Organizational Rewards and Performance of Health Centre IV Workers in Greater Mbarara District, Uganda - Atwiine, Johnson; Atukunda, Gershom; Tumwesigye, Wycliffe; Asasira, Justus (Research square, 2020)
Purpose: The purpose of this paper is to study relationship between organizational rewards, and performance of Health Centre IV workers in greater Mbarara District. Methods: This study used cross-sectional, explanatory and correlational approaches, and it utilised health center IV’s workers’ data that were collected by using a questionnaire survey from a sample of 200 health workers from 11 health centres from greater Mbarara district. Findings: Results revealed that rewards, were significantly associated with health workers’ performances. Contrary to previous thinking, organizational rewards and constructs do not significantly predict health workers’ performance. Once health centre IV’s have appropriate reward strategies for their health workers in health facilities, they are likely to work hard by meeting deadlines, being available at their work station and they would eventually enhance on job performance. Research limitations/implications: This study focuses on rewards, and performance of health workers’ in health centres iv in greater Mbarara and it is possible that these results are only applicable to the public health centres iv in greater Mbarara. More research is therefore needed to further understand the relationship between rewards, and performance of health workers in other sectors such as the private health sector and in other areas of the country like northern, central and eastern Uganda. Practical implications: The results are important for health policy development and implementation, for example, in terms of primary health care and reporting lines for the health workers so as to enhance on their performance in public health sector. Originality/value: As far as the authors are aware, no research has hitherto been undertaken that investigates the relationship between reward practices on health workers’ performance in health centres IV in greater Mbarara district. Thus the results of this study will provide health practitioners with better insights in some reward practices that could be adopted by government/health practitioners so as to improve the performance of health centres IV workers
Keywords: Organizational rewards; Performance of Health Center IV Workers